Effective Primary Prevention of Atopic Dermatitis in High-Risk Neonates via Moisturizer Application: Protocol for a Randomized, Blinded, Parallel, Three-Group, Phase II Trial (PAF Study) - Inuzuka, Yusuke; Yamamoto-Hanada, Kiwako; Pak, Kyongsun; Miyoshi, Takekazu; Kobayashi, Tohru; Ohya, Yukihiro (Frontiers in Allergy, 2022)
Background Atopic dermatitis (AD) is a chronic and inflammatory skin disease that causes health-related burdens associated with pruritus and poor quality of life. Our previous study demonstrated that moisturizer (2e) application has a primary preventive effect on AD. However, this effect was not observed in recent randomized control trials. Thus, the ideal moisturizer type and application frequency for preventing AD development in infants remains unclear. We hypothesize that twice daily application of moisturizer is more effective than once daily application. We predict that applying sufficient amounts of high-quality moisturizer may be effective for preventing AD development in neonates and infants. Here, we describe a protocol for comparing the efficacy of twice daily and once daily application of Fam's Baby™ moisturizer and once daily application of 2e moisturizer for preventing AD in neonates. Methods This study is a single-center, three-parallel group, assessor-blind, superiority, individually randomized, controlled, phase II trial. Sixty newborns with at least one parent or sibling who has had AD is randomly assigned to application of Fam's Baby twice daily, Fam's Baby once daily, or 2e once daily in a 1:1:1 ratio until 32 weeks old. The primary outcome is the time to the first onset of AD during administration of the moisturizer. Discussion This is the first phase II randomized, controlled trial in Japan to estimate how effective the twice daily or once daily application of Fam's Baby moisturizer is in preventing AD compared to the once daily application of 2e moisturizer. In this study, we will use 2e once daily as a control to confirm the efficacy for primary prevention of AD as found in our previous trial. Based on the results of this study, we hope to conduct a phase III study to determine the optimal method for preventing AD via moisturizer application. Evaluation of application of moisturizers for preventing AD in this study is expected to contribute to a reduction in the prevalence of AD and a reduction in health care costs. Trial registration Japan Registry of Clinical Trials (jRCT); ID: jRCTs031200070.